Modified- versus immediate-release tofacitinib in Japanese rheumatoid arthritis patients: a randomized, phase III, non-inferiority study. (17th August 2018) - Tanaka, Yoshiya; Sugiyama, Naonobu; Toyoizumi, Shigeyuki; Lukic, Tatjana; Lamba, Manisha; Zhang, Richard; Chen, Connie; Stock, Thomas; Valdez, Hernan; Mojcik, Christopher; Fan, Haiyun; Deng, Chenhui; et al.
Abstract: Objective: Tofacitinib is an oral Janus kinase inhibitor for treatment of RA. We compared tofacitinib modified-release (MR) 11 mg once daily (QD) with tofacitinib immediate-release (IR) 5 mg twice daily (BID) in Japanese patients with RA and inadequate response to MTX. Methods: Phase III, randomized, double-blind, double-dummy, 12-week study. Patients were randomized to tofacitinib MR 11 mg QD ( n = 104) or IR 5 mg BID ( n = 105), with stable MTX. Compliance was based on returned pill counts. The primary objective was to demonstrate non-inferiority of MR 11 mg QD to IR 5 mg BID. Non-inferiority was declared if the upper bound of the two-sided 95% CI for the difference in change from baseline in DAS28-4(CRP) at week 12 was <0.6. Results: At week 12, with tofacitinib MR 11 mg QD and IR 5 mg BID, respectively, the change from baseline in least squares mean DAS28-4(CRP) was −2.43 and −2.85; the mean difference was 0.43 (95% CI 0.17, 0.69). Non-inferiority of MR 11 mg QD to IR 5 mg BID was not met. Improvement of DAS28-4(CRP) ⩾1.2 was observed in 89 and 85% of patients, respectively, corresponding to a clinically important, significant change in both groups. The frequency of adverse events (52.9 and 51.4%, respectively) and serious adverse events (4.8 and 3.8%, respectively) was generally similar between treatments. No deaths were reported. Conclusion: Non-inferiority of MR 11 mg QD to IR 5 mg BID was not met in this study. However, clinically meaningful improvements in RA were observed with both tofacitinib formulations in Japanese patients. The safety profile was similar with both formulations. Trial registration: ClinicalTrials.gov, http://clinicaltrials.gov, NCT02281552.